ChemInform Abstract: Poly(2‐oxazoline) Functionalized Surfaces: From Modification to Application. Issue 50 (10th December 2013) - Tauhardt, Lutz; Kempe, Kristian; Gottschaldt, Michael; Schubert, Ulrich S.
Abstract Review: different approaches to immobilize the title biocompatible polymers on surfaces as well as properties and applications; 50 refs.